Mengungkap Dampak Ukuran, Struktur Modal, dan Pertumbuhan terhadap Nilai Perusahaan Manufaktur: Pendekatan Baru - Juniarto, Antonius; Tyas, Isthi Wahyuning; Wicaksono, Dading Damas Ario (International Journal of Digital Entrepreneurship and Business, 2024)
Achieving investment success requires a thorough understanding of a company’s intrinsic value, as strategic investment decisions often hinge on the accurate valuation of the target company. Recognizing this, companies must continually enhance their value to attract potential investors. This study sought to empirically assess the influence of company size, capital structure, and growth on the value of manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2014 to 2016. The research employed purposive sampling methods to gather data and utilized multiple linear regression analysis through SPSS software for statistical evaluation to meet this objective. The findings indicated that both company size and growth had a significant positive impact on company value, whereas capital structure did not show a significant effect. Moreover, the results of simultaneous testing revealed that the combination of capital structure, company size, and growth had a significant collective influence on the value of the companies. These insights underscore the importance of focusing on company size and growth strategies to enhance firm value in the eyes of investors.